B-vitamin nutrition in the pea aphid-Buchnera symbiosis. (October 2020) - Blow, Frances; Bueno, Eduardo; Clark, Noah; Zhu, Dan Tong; Chung, Seung Ho; Güllert, Simon; Schmitz, Ruth A.; Douglas, Angela E.
Graphical abstract: Highlights: Buchnera has the genetic capacity to synthesize vitamins B2 and B5 . Aphids performed poorly on diets lacking B5, but not other B vitamins. Buchnera has antisense transcription against terminal B5 biosynthesis genes. Gene content does not predict B vitamin nutrition in the aphid- Buchnera symbiosis. Abstract: Various insects that utilize vitamin-deficient diets derive a supplementary supply of these micronutrients from their symbiotic microorganisms. Here, we tested the inference from genome annotation that the symbiotic bacterium Buchnera aphidicola in the pea aphid Acyrthosiphon pisum provides the insect with vitamins B2 and B5 but no other B-vitamins. Contrary to expectation, aphid survival over five days of larval development on artificial diets individually lacking each B-vitamin not synthesized by Buchnera was not significantly reduced, despite significantly lower carcass B1, B3, B6 and B7 concentrations in the aphids on diets lacking each of these B-vitamins than on the vitamin-complete diet. Aphid survival was, however, significantly reduced on diet containing low concentrations (≤0.2 mM) or no pantothenate (B5 ). Complementary transcriptome analysis revealed low abundance of the sense-transcript, but high abundance of the antisense transcript, of the Buchnera gene panC encoding the enzyme mediating the terminal reaction in pantothenate synthesis. We hypothesize that metabolic constraints or antisense transcripts may reduce Buchnera -mediated production of pantothenate, resulting in poor aphid performance on pantothenate-free diets. The discrepancy between predictions from genome data and empirical data illustrates the need for physiological study to test functional inferences made from genome annotations.